Typical pharmacovigilance system master file (PSMF) - B. K. Romanov; R. N. Alyautdin; S. V. Glagolev; V. A. Polivanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
The typical pharmacovigilance system master file (PSMF) is presented. MPSF was created on the basis of the Rules of good pharmacovigilance practice for the members of Eurasian economic Union countries. Possible ways of the description of the pharmacovigilance system, all the possible types of MPSP and constituent standard operating procedures are considered. Practical recommendations on preparation and using of MFSF are given.